2016
DOI: 10.1080/1354750x.2016.1204006
|View full text |Cite
|
Sign up to set email alerts
|

Base excision repair pathway:PARP1genotypes as modulators of therapy response in cervical cancer patients

Abstract: This is the first study evaluating the effect of PARP1 Val762Ala polymorphism in treatment response in cervical cancer patients. PARP1 genotypes may contribute as an independent prognostic factor in cervical cancer, being useful in predicting the clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
0
5
1
Order By: Relevance
“…It was reported that peri- and postmenopausal women carrying the C-allele of the PARP-1 Val762Ala polymorphism (rs1136410) present a statistically significant lower OS and disease-free survival (DFS) among those with early-stage cervical cancer. 31 In the previous meta-analysis, PARP-1 polymorphism (rs1136410: T > C) was also noted to be a risk factor for gastrointestinal cancers in an Asian population, but not in a Caucasian population. 32 PARP-1 would be an advantageous indicator of the disease for population studies.…”
Section: Discussionmentioning
confidence: 93%
“…It was reported that peri- and postmenopausal women carrying the C-allele of the PARP-1 Val762Ala polymorphism (rs1136410) present a statistically significant lower OS and disease-free survival (DFS) among those with early-stage cervical cancer. 31 In the previous meta-analysis, PARP-1 polymorphism (rs1136410: T > C) was also noted to be a risk factor for gastrointestinal cancers in an Asian population, but not in a Caucasian population. 32 PARP-1 would be an advantageous indicator of the disease for population studies.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, in the present study, our results demonstrate a significant association between PARP1 rs1136410 and lymph node involvement in gallbladder cancer patients. However, a significant association was not found between genotypes of PARP1 rs1136410 and lymph node involvement in cervical cancer patients (Roszak et al , 2013; Nogueira et al , 2017).…”
Section: Discussionmentioning
confidence: 84%
“…Studies are currently being carried out to investigate potential suppressors of survival pathways and promoters of apoptotic pathways as novel chemotherapy approaches for the treatment of cervical cancer [ 33 ]. An association between poly ADP-ribose polymerase 1 (PARP1) Val762Ala polymorphism (rs1136410) and cancer therapy response has been identified, and PARP1 genotypes have been proposed to be an independent prognostic factor in cervical cancer [ 34 ]. In addition, it has been shown that PARP-1 inhibition may augment cisplatin cytotoxicity in cervical cancer cells by diminishing DNA repair and suppressing β-catenin signaling pathway [ 35 ].…”
Section: Discussionmentioning
confidence: 99%